Answer to Question #5975 in Calculus for Samantha
Due to the statement of the question f(x) = x/(x - 6)
To obtain function composition (f*g)(x)=f(g(x)) we have to substitute g(x) instead of x into the expression for
as f(x) = x/(x - 6)
we have (f*g)(x) = f(g(x)) = g(x)/[g(x) - 6].
And the last expression has to be equal to x:
g(x)/[g(x) - 6]=x
g(x) = xg(x) - 6x, so (x - 1)g(x) = 6x, and g(x) = 6x/(x - 1). Thus, g(x) is the inverse of f(x).
For you and other our visitors we created this video. Please take a look !
Need a fast expert's response?Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!